Muslim Prosperous Family (MPF) Consumption in Koto Tuo Ujung Pasir Village: Is It Consistent with Islamic Consumption Behaviour? - Fauzi, Muhammad; Kurniawan, Mhd. (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2023)
This study aims to see the consumption behaviour of Muslim Prosperous Family (MPF) in Koto Tuo Ujung Pasir Village in line (consistent) with consumption behaviour Islamic economic. This study uses a qualitative approach, and data sources are collected from primary sources using Miles and Huberman model as a data analysis tool. The results of this study show consumption behaviour of MPF is in line with the consumption behaviour of Islamic economics, it can be seen from of balanced behaviour in consumption (such consumption for oneself, family, and Fisabilillah), spending wealth in halal and good ways. However, there are still some consumption behaviours of MPF that are not in line with consumption behaviour Islamic economics, it can be seen from in form of behaviour for oneself and the family that reflects more wasteful (Tabzir), royal (Israf), and also makes Ribawi loans at Conventional Banks in order to obtain luxury goods. This study can add to the existing reading of Islamic economics literature, because this study is based on the theory and concept of consumption behavior in Islamic economics to see MPF consumption behavior. This study also has many limitations, so it is open for further research to examine it in depth.